Pengaruh ukuran perusahaan, pertumbuhan perusahaan, kebijakan hutang, masa perikatan audit, umur perusahaan dan kerugian perusahaan terhadap kualitas audit - Lydia; Hermanto (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study examines the relationship between company size, company growth, leverage, audit partner tenure, firm age, company losses and audit quality. The data in this research used food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX) for 4 research year periods, from 2018 to 2021. Where data were obtained from 72 of 18 food and beverage subsectors with 4 years of observation. This research uses secondary data collected through the company's official website and the Indonesia Stock Exchange. Purposive sampling method is used to select a sample of companies. Research results prove that company size, debt policy (leverage) have a significant negative impact on audit quality, while company growth, audit engagement period, firm age and company losses have a positive impact on audit quality.